Product Quality of the Local Food Rempeyek in Palu City, Indonesia - Yusma Indah Jayadi; Ayu Astari (Public Health Department, Universitas Islam Negeri Alauddin Makassar, 2022)
Peanuts are one of the agricultural products that are a source of protein and vegetable oil. In Indonesia, peanuts are widely consumed and processed into complementary foods or snacks. Peanut cracker is a typical Indonesian food that is liked by all people. The main ingredient in making peanut brittle is using peanuts which have the potential for pathogen contamination. his study is a descriptive observational cross sectional study that aims to analyze GMP (Good Manufacturing Practice) and HACCP (Hazard Analysis Critical Control Point) in one of the SMEs (Small and Medium Enterprises) in Palu City with a product that is peanut brittle. GMP analysis was carried out using the Self-Assessment Questionnaire created by Food Supplement Europe and assessed on the Gutman scale. The results of the analysis show that UKM X still poor at <50% in implementing GMP. HACCP analysis shows that there is a CCP (Critical Control Point) in the process of making peanut brittle, namely during the frying process, peanut washing and sorting. Keywords: Peanuts, Indonesian Food, Good Manufacturing Practices, Hazard Analysis Critical Control Point.